Bloom Nutrition Influencer Marketing Analysis - Jackson, Kirsten (My University, 2023)
This project is a marketing analysis of Bloom Nutrition's use of influencers to sell products to Gen Z consumers interested in wellness. Bloom’s marketing team works with a diverse group of influencers to reach potential customers. Upon initial review, each influencer seems to have a vastly different approach to creating content and engaging audiences around Bloom products. Therefore, the purpose of this study is to identify which influencers and their associated strategies work best for this brand and within the industry. Within this study I will analyze Bloom’s influencer marketing strategy through a content analysis on TikTok that includes identifying influencer tactics of four key influencers that the brand has used. Information gathered about these influencers will be their audience, follower counts, credibility, and the type of content that they share. I will also look at the consumer responses to influencer content to identify the interaction and engagement that each post received and how well the content performed through sentiment analysis. At the conclusion of this study, I will ultimately produce an ideal influencer profile for the fitness/wellness industry and for the brand Bloom.